Anisotropic mechanical and fatigue behaviour of Inconel718 produced by SLM in LCF and high‐temperature conditions. Issue 1 (6th November 2020) - Sausto, F.; Marchese, G.; Bassini, E.; Calandri, M.; Biamino, S.; Ugues, D.; Foletti, S.; Beretta, S.
Abstract: Additive manufacturing (AM) is one of the processes with the most potential for producing components used in internal combustion engines and features high efficiency due to the possibility of building very complex shapes. Several drawbacks of parts produced using AM are still unresolved, like poor surface quality, the presence of internal defects and anisotropic mechanical behaviour, which all contribute to decreasing the fatigue strength compared with the material produced using conventional processes. The effect of building direction on both the macroscopic mechanical behaviour and the crack propagation mechanism of Ni‐base superalloy Inconel718 produced using AM was investigated under the combined effect of low cycle fatigue (LCF) and high temperature. The different crack growth mechanisms investigated using compact tension (CT) specimens, tested at high temperature, showed a significant difference between the two building directions. The LCF fatigue experiments also showed a significant difference in the ε‐N curves from the two directions together with a high level of scatter due to the dispersion of the defect size at the fracture origin. The dimensions of the defects (as measured using the area parameter) were analysed by means of extreme value statistics and showed a significant difference between the two orientations investigated. The aim of this work is to propose a simplified approach (based on Δ J eff concepts) to estimate the fatigue life of a component produced using AM that takes into account the material variability due to the combined effect of mechanical anisotropic behaviour and the presence of defects at high‐temperature conditions.